Filial piety and family relationships of two generations of Vietnamese parents - Bui, Tuoi Thi (Animo Repository, 2006)
This study investigated the concept and indicators of filial piety and family relationship among two generations of Vietnamese parents using a qualitative research design with in-depth interview and case study. The participants of the study were ten households, each consisting of a first generation of parents and a second generation of parents. The study found that filial piety was practiced in both generations even today. Three theme clusters were arrived at namely customary, exceptional, and venerable filial piety. Under each theme cluster were several themes. Customary filial piety was defined as symbolic displays of respect towards not only parents but also other elder namely being obedient to parents, gifts offering, greeting parents, using respectful language, and saving the honorable place for parents. Exceptional filial piety consisted of behavior drawing favorable attention and affection to parents, including looking after parents’ mental and physical health, seeking advice of parents, spending time with parents, and serving food and drinks of parents’ choice. Finally, venerable filial piety was shown to be culturally based, such as venerating ancestors and holding parents’ funeral rites. Filial piety practices were reflected in family relationships in which children expressed deep gratitude to their parents for the gift of life, for rearing them and educating them from the past until present. Filial piety was also manifested in hierarchical family relationships where parents and parents-in-law were revered and respected.